(untitled) (Revista de Ciências Agroveterinárias, 2018)
The intensive and repeated use of the chemical control method in the wheat crop selected populations of turnip (Raphanus raphanistrum and R. sativus) and ryegrass (Lolium multiflorum) resistant to herbicides, especially from the groups of ALS‑, ACCase‑ and EPSPS‑inhibitors. It is important to rotate the herbicide mechanisms of action to manage populations of resistant weeds, both in burndown and after planting. Thus, this work aimed to assess the effectiveness of the herbicide clomazone in the control of ryegrass and turnip associated or not to dietholate safener protection in wheat crop. The first experiment was conducted in a completely randomized design (CRD), with four replications. Dietholate doses (0, 120, 240, 360 and 480 g per 100 kg of seeds of wheat cultivar TBIO Itaipu) were associated to clomazone doses (0, 198, 396 and 594 g ha‑1) sprayed pre-emergence. The second experiment comprised infested and weeded control treatments, the pre-emergence application of clomazone + dietholate (396 g ha-1 + 240 g per 100 kg seed) and post-emergence application of iodosulfuron-methyl (5 g ha-1) or pyroxsulam (18 g ha-1). The treatment of wheat seeds with dietholate did not affect the control of ryegrass and turnip by clomazone when applied pre-emergence. Clomazone, even when sprayed at low doses, presented ryegrass control above 80% and can be used to control resistant biotypes of this weed to EPSPs‑, ALS‑ and ACCase‑inhibitors. Iodosulfuron-methyl and pyroxsulam showed excellent control of turnip and satisfactory control of ryegrass.